GENETIC AND MOLECULAR ANALYSIS OF COMPLEMENTATION OF THE FLAMENCO AND PIWI LOCI IN DROSOPHILA MELANOGASTER - F. A. Urusov; L. N. Nefedova; A. R. Lavrenov; N. I. Romanova; A. I. Kim (Вавиловский журнал генетики и селекции)
It is believed that the heterochromatic locus flamenco, controlling transposition of retrotransposon/retrovirus gypsy in Drosophila melanogaster, is a source of Piwi-interacting RNA. Piwi is the primary component of the RNA interference machinery. Mutations in piwi and flamenco have the same phenotype – an enhanced transcription and frequency of transposition of the retrotransposon/retrovirus gypsy. This paper discusses the results of the complementation test, which involves crossing strains MS and SS, mutant for the flamenco locus, with the piwi strain 3, heterozygous for a mutation in the piwi gene, followed by study of the transcription level of gypsy in the ovaries and testes of hybrids derived from these crosses. Genetic (hybridological) and molecular analysis of the interaction of the flamenco and piwi loci has been conducted. It has been revealed that transcription of gypsy is differently regulated in testis and ovaries of strains SS and MS, apparently owing to the different activity of piRNA clusters in these tissues. It has been also shown that the piwi and flamenco genes interact complementarily in testis tissue.